Dynamic changes in autophagosome formation and lipid droplet accumulation during spermiogenesis in mice - YANG Yixuan, QIAN Xiaojing, LIU Zhenghui, HAN Daishu, CHEN Yongmei (Jichu yixue yu linchuang)
Objective To investigate the temporal and spatial relationship between autophagosome formation during spermatid deformation and lipid droplet distribution in seminiferous tubules, thereby providing insights into the energy sources underlying spermiogenesis. Methods Healthy adult wild-type male mice were used in this study. The expression profile of the autophagy marker microtubule-associated protein light chain 3 (LC3) in the testis was examined using immunohistochemical staining and Western blot. The ultrastructural features of autophagosomes were observed via transmission electron microscopy. Lipid droplets in the seminiferous tubules were visualized by Oil Red O staining, and the relationship between lipid metabolism and energy dynamics was assessed by measuring ATP content and ATPase activity. Results Autophagosomes were detected in deforming spermatids and Sertoli cells. LC3 was predominantly expressed in the cytoplasm of elongating spermatids, with increasing levels found from stages Ⅱ to Ⅳ. Concurrently, lipid droplets within these cells also increased, peaking in spermatids and residual bodies during stages Ⅶ-Ⅷ, followed by a decline. In contrast, lipid droplets in Sertoli cells remained markedly increased during stages Ⅸ-Ⅰ and low during stages Ⅱ-Ⅷ. The change of ATP levels in the seminiferous tubules showed a similar pattern as Sertoli cell lipid content, whereas ATPase activity showed an inverse trend. All these changes displayed a clear stage-dependent manner. Conclusions During spermatid elongation in mice LC3 expression, autophagosome formation, lipid droplet accumulation in both spermatozoa and Sertoli cells, as well as ATP and ATPase levels in seminiferous tubules exhibit a tightly coordinated spatiotemporal relationship. These findings suggest that autophagy and lipid metabolism synergistically contribute to the energy supply required for the extensive cellular remodeling that occurs during spermiogenesis.